HUBUNGAN PENGGUNAAN GADGET DENGAN KEBUGARAN FISIK SISWA SMA - Ahmad Rizal Fadhlan; Desty Endrawati Subroto; Tubagus Lucky Tri Iman Setiawan; Ahmad Firdaus; Wahyudi Wahyudi; Gabriela Talasari Sumbayak; Ahmad Fikri (Jurnal Padamu Negeri, 2025)
In the current era of globalization, science and technology are developing rapidly. One example of very popular technology is gadgets. Gadgets have a positive impact on children's thinking patterns, such as helping them regulate the tempo when playing, designing strategies in games, and improving right brain abilities. Notwithstanding these benefits, the use of gadgets can have detrimental effects on children's development, with a heightened impact on teenagers. The radiation produced by gadgets can damage a child's nerve tissue and brain if used too often. More importantly, children become less mobile and are rarely exposed to sunlight, which affects their physical health. As a result, children tend to become less interactive, less creative, and more comfortable being alone with their gadgets. This can trigger individualistic attitudes and reduce feelings of concern for parents, friends and other people around them, as well as their physical health. Physical education and sports carried out in the right proportions can make children fitter, so they can remain active and productive.